Academia–Industry Partnerships for Hospitality and Tourism Education in Tanzania. Issue 1 (2nd January 2019) - Anderson, Wineaster; Sanga, John J.
ABSTRACT: This article examines approaches to partnership between the tourism industry and educational institutions in the provision of tourism education. It assesses how partnerships facilitate the development of skills in Tanzania and recommends a framework for effective collaboration. The study utilized focus group discussions and interviews with tourism industry and training institutions. A total of 356 respondents participated. It was revealed that internships, practical training, graduate employment, and financial contributions by industry in the form of skills development levy and tourism development levy are the major approaches to partnership for the provision of tourism education. A low level of understanding among students explained by language barriers, inadequate training facilities, a shortage of qualified educators, poor enforcement of national curricula, and limited internship and placement opportunities are the major challenges to skills development. The article proposes a framework for effective partnership among key stakeholders in the industry.